The Influence of Work Motivation and Job Satisfaction on Employee Performance with Work Discipline as an Intervening Variable at the Directorate General of Sea Transportation - Imron Nur Halim; Corry Yohana; Christian Wiradendi Wolor (International Journal of Economics, Management and Accounting (IJEMA), 2023)
This research aims to determine the influence of work motivation and job satisfaction on employee performance with work discipline as an intervening variable at the Directorate General of Sea Transportation, Ministry of Transportation of the Republic of Indonesia. This research uses a quantitative type of research using a population of 137 people with a sample of 102 employees at the Directorate General of Sea Transportation, Ministry of Transportation of the Republic of Indonesia. Data collection techniques use questionnaires, observation and literature study. Data analysis uses Partial Least Square (PLS) with the SMARPLS 4.0 application. The results of the research show that work motivation has a positive and significant effect on employee performance, work motivation has a positive and significant effect on work discipline, job satisfaction has a positive and insignificant effect on employee performance, job satisfaction has a positive and significant effect on work discipline, work discipline can mediate or mediating the influence of work motivation on employee performance, work discipline can mediate or mediate the influence of job satisfaction on employee performance.